Starvation-induced cell fusion and heterokaryosis frequently escape imperfect allorecognition systems in an asexual fungal pathogen - Vangalis, Vasileios; Likhotkin, Ilya; Knop, Michael; Typas, Milton A.; Papaioannou, Ioannis A. (BMC biology, 2021)
Asexual fungi include important pathogens of plants and other organisms, and their effective management requires understanding of their evolutionary dynamics. Genetic recombination is critical for adaptability and could be achieved via heterokaryosis — the co-existence of genetically different nuclei in a cell resulting from fusion of non-self spores or hyphae — and the parasexual cycle in the absence of sexual reproduction. Fusion between different strains and establishment of viable heterokaryons are believed to be rare due to non-self recognition systems. Here, we investigate the extent and mechanisms of cell fusion and heterokaryosis in the important asexual plant pathogen Verticillium dahliae.